The Effect of Back-Up on the Strength of Throwing in Football at Students X MAN Pangkalan Balai, Banyuasin - Suwinto, Suwinto; Akhbar, M Taheri (Yayasan Sembilan Pemuda Indonesia, 2023)
Based on the results of the researchers’ observations of the basic techniques mentioned above, technically and the abilities of the students were still far from being in the good category, one example being the throw-in ability. In terms of what is known, a throw-in can be used as bait to score a goal if the ball is thrown into the mouth of the goal and bait using a throw-in is often used to create a goal. The method used in this study was an experimental method with the research subjects being class X students Islamic Senior High School Pangkalan Balai of Banyuasin District who took part in extracurricular football games with a total of 30 male students. The data collection technique used is the test technique, namely the initial test and posttest. As for the test instrument is the throw-in to the game of football. Based on the results of research that has been conducted on students of MAN Pangkalan Balai Banyuasin Regency, regarding the effect of back-up training on throwing into a football game, the statistical results obtained in the hypothesis test are that t count is greater than t table (49.5> 2.045) with a confidence level 0.05% for a sample of 30 (dk = n-1 = 29) it is a rule that if t count > t table, then Ha (Hypothesis accepted) and vice versa if t count <t table, then Ho (Hypothesis rejected). So that it can be concluded that the hypothesis states there is an effect of back-up training on the ability to throw in the game of football in students of X Islamic Senior High School Pangkalan Balai of Banyuasin District.